To solve this equation, we need to find a common denominator for the fractions on both sides.
Start fraction 1/3x + 9 end fraction - start fraction 2/x + 3 end fraction = 2
The common denominator for 3x and x is 3x. So, we rewrite the equation with this common denominator:
(1( x + 3) - 2(3))/(3 x) = 2
Now we simplify the equation:
(x + 3 - 6)/(3x) = 2
(x - 3)/(3x) = 2
Now we cross multiply to get rid of the fraction:
x - 3 = 6x
Next, we solve for x:
x - 3 = 3x
Subtract x from both sides:
-3 = 2x
Now divide by 2 to solve for x:
x = -3/2
Therefore, the solution to the equation is x = -3/2.
Solve.
start fraction 1 over 3 x plus 9 end fraction minus start fraction 2 over x plus 3 end fraction equals 2
1 answer